Que la casa os sea leve. La memoria de la casa encantada y la represión de la bruja a través de Carcoma, de Layla Martínez - García, Noelia S. (Studia Romanica Posnaniensia, 2026)
This work analyzes the novel Carcoma (2021) by Layla Martínez taking into account the relationship the witch establishes with the space she inhabits. Primarily, the figure of the witch will be reinterpreted in light of feminist theories, considering her as a repository of recent historical memory. Secondly, special attention will be paid to the witch’s house, understood as a restorative entity which allows the main characters to articulate both their revenge and the process of reparation as victims of repressive violence exerted by various social agents.